Changes in viable bacterial counts and physicochemical parameters of water used during live transportation of Pangasius catfish (Pangasianodon hypophthalmus) in Bangladesh - Bhuiyan, A N M Rezvi Kaysar; Hossain, Md Mubarack; Uddin, Md Naim; Hossain, Md Anwar; Hossain, Md Ismail; Haider, Md Nurul (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The study was undertaken to assess the changes in viable bacterial counts and physicochemical parameters of water used during the live transportation of Pangasius catfish (Pangasianodon hypophthalmus). The correlations between the changing patterns of these parameters were also established. Materials and Methods: Water samples were collected every 2 h interval, plated onto agar plates for assessing viable bacterial counts. Physicochemical parameters, namely, water temperature, dissolved oxygen (DO), pH, and ammonia (NH3 ) concentration in the water were measured with a glass thermometer, DO test kit, pH test kit, and total NH3 measurement kit, respectively. Results: The viable bacterial counts increased significantly from 0 to 2 h in all the studied channels and remained almost similar up to the end of the supply channels. The water temperature was almost stable regardless of the supply channels and transportation period at around 30°C. The DO concentration and pH level decreased, and NH3 concentrations increased gradually in all the supply channels. The viable bacterial counts were inversely correlated to the DO levels and directly associated with the NH3 concentrations of the water used during the live transportation of Pangasius catfish. Conclusions: Gradual increase in viable bacterial counts and fluctuation in some vital physicochemical parameters with the duration of transportation indicated an unfavorable environment for the survival of Pangasius catfish. J. Adv. Vet. Anim. Res., 9(1): 66–77, March 2022 http://doi.org/10.5455/javar.2022.i570